A comparasion of bracket debonding forces between the two adhesives: Con Tec LC and Con Tec Duo - Mirjanić, V.; Mirjanić, S.; Čupić, S; Jesic, Dusan (Journal of Production Engineering, 2023)
Fixed technique for applying brackets would be impossible without using adhesives for their fixation to the tooth enamel. However, the use of adhesives entails a number of problems which are a consequence of their imperfection, besides the fact that they have been actually applied for a number of decades already. The paper will analyze the debonding force values for bracket-tooth interface by using Con Tec LC and, Con Tec Duo. For comparative analysis of the strength of bracket-tooth interface, with the application of different types of adhesives, 80 extracted teeth of the frontal region were used (central, lateral incisor teeth and canines of the upper and lower tooth arch). For the debonding process of applied orthodontics brackets, single-axial Stretch system for examination of tissues was applied to determine the value of the force necessary to separate the bracket from tooth surface, i.e. it was used to test debonding force. The direction of the used force for debonding was under angle of 90 degrees to the vertical axis of the tooth. By comparison of mean values of the strength of interface among the tested groups, it was determined that the highest average value of bond strength was with the group of teeth with which Con Tec Duo was used, a little lower mean value was recorded with the use of Con Tec LC adhesive.